Um programa para aprimorar envolvimento paterno : impactos no desenvolvimento do filho - Cia, Fabiana (Universidade Federal de São Carlos, 2009)
Children who do not have a positive, secure and affectionate relationship with their fathers, or whose fathers use rigid disciplinary practices, provide inadequate supervision and have infrequent or poor quality interactions with their children, are at greater risk for developing socio-emotional problems and for remaining at lower levels of academic achievement. However, the majority of fathers have little understanding of the importance of their involvement with their children. As such, the primary objective of this study was to evaluate a program designed to improve father involvement and to stimulate the use of parenting practices that foster children s pro-academic behaviors, using measures obtained before and after the intervention as well as one year later (follow-up). The specific objectives included: (a) the comparison of indicators of work conditions, personal and family wellbeing, father involvement and the parents social skills on the pre, post and follow-up tests among the Experimental Group 1 (EG1 composed of fathers who were randomly selected to participate in the intervention program), Experimental Group 2 (EG2 composed of randomly selected mothers who participated in the intervention program) and a Control Group (the remaining, waitlisted parents); (b) comparison of the academic achievement, self concept, behavior problems and social skills of their children at the time of the pre, post and follow-up tests, for those in the EG1, EG2 and CG; (c) examination of the strength of the correlations among these variables, and (d) analysis of parent evaluations of the topics that were addressed and the procedures used in the intervention program. At the times of the pre and post-tests, parent participants included 97 father-mother pairs (29 in the EG1, 34 in the EG2 and 34 in the CG) and 82 of these father-mother pairs at the time of the follow-up tests (24 in the EG1, 29 in the EG2 and 27 in the CG). At the time of the pre and post-tests, data were also obtained from 99 children (there were two sets of twins) 29 from the EG1, 36 from the EG2 and 34 from the CG. At the time of the pretest, these children were eight years old, on average, and 78,8% of them were in Grade 2 while the others were in Grade 1. At the time of the follow-up tests, 84 of these children were re-evaluated (24 from the EG1, 31 from the EG2 and 27 from the CG). In addition, in the first year of the study, 20 teachers (85% of whom had completed university studies) participated in the pre and pos-test phases and a second set of 12 teachers (all of whom had completed university studies) participated in the follow-up phase, given that the children had advanced to the next grade between the post-test and the follow-up. Data were collected with children from three different, public elementary-schools. The intervention program was conducted with the parents during 12 weekly sessions that were 90 120 minutes long, with the GE1 fathers and GE2 mothers. To address the objectives of this study: (a) the parents evaluated their work conditions, their personal and family wellbeing and their social skills repertoire; (b) both parents and their child evaluated the father s level of involvement as a parent; (c) the children s academic achievement, self concept and social skills were assessed; (d) both parents evaluated their child s behavior problems and social skills repertoire; (e) the teachers evaluated the children s academic achievement, behavior problems and social skills, and (f) the fathers from the EG1 and the mothers from the EG2 evaluated the intervention program. Statistical testes (ANOVA and MANOVA) were used to compare the data obtained in the three different phases of the study, for each of the three different types of informants (parents, children and teachers). Pearson correlations were used to examine the bivariate relationships among these variables. With respect to the first objective, comparisons of the results on the pre and post-intervention tests revealed that the fathers in the EG1 were significantly less stressed and there was a significant decrease in the number of disagreeable behaviors that their children presented; both the GE1 and GE2 fathers presented greater satisfaction with respect to their family-role performance, higher frequency of communication with their child, greater frequency of participation in school, cultural and leisure activities with their child, greater participation in school meetings concerning their child, more frequent contact with their child s teacher and listed a greater number of their child s behaviors that pleased them. In terms of the children s gains, a comparison of the pre and post-test results indicate that children in the EG1 presented: (a) higher scores on the Academic Achievement Test (AAT) with respect to the reading sub-test and their overall score, along with higher teacher evaluations of their academic performance; (b) a lower number of internalizing behavior problems (according to their fathers), externalizing and total problems (according to both parents); (c) social skills that were more adequate with respect to self control (for both self and father ratings) and self defense (according to the teachers), and (d) more positive teacher evaluations, across various indicators. Similarly, in comparison with the pre-test, on the post-test, children in the EG2 presented: (a) higher scores on the Academic Achievement Test (AAT) with respect to the reading sub-test and their overall score, along with higher teacher evaluations of their academic performance; (b) a lower number of externalizing and total problems (according to both parents); (c) social skills that were more adequate with respect to Cooperativeness and Self control (according to their fathers) Assertiveness in their coping strategies (according to their mothers), and Cooperation with peers (according to the teachers), and (d) more positive teacher evaluations, across various indicators. The majority of the gains obtained by the fathers and their children by the end of the intervention program were maintained or further improved at the time of the follow-up tests, with the exception of the children s self-evaluations of their social skills on the Self control factor, for which there was a significant decline between the post-test and follow-up test. With respect to the third objective, father involvement was significantly correlated with the children s academic performance, self concept, externalizing behavior problems and social skills, and measures involving the children were significantly inter-correlated. Finally, in general, the intervention program helped the fathers (EG1) and mothers (EG2) in bringing up their children. For example, some parents (22,2%) commented that it became easier for them to deal with the difficulties of parenting, while others (19%) were better able to handle their children s behavior problems, occurring either at home or at school. The parents attributed various important contributions to the intervention program: 27% changed their parenting behaviors, 19% were giving greater importance to their child s opinions and 15.9% commented that their child was more obedient. With respect to the parents acquisition of new social educational skills, 31.7% said that they learned about the importance of respecting their child s opinion and 30.2% said that they learned to set limits for their children. These results indicate the importance of educational interventions for maximizing parental involvement and, as a consequence, improving their children s social emotional development and classroom behavior.
Keywords: Educação especial; Programa de intervenção; Educação - participação dos pais; Desempenho acadêmico; Problemas de comportamento; Desenvolvimento emocional; Autoconceito; Intervention; Father involvement; Self concept; Academic achievement; Behavior problems; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL